ANALISIS PELAKSANAAN BIMBINGAN PADA KESULITAN BELAJAR SISWA - Reni Wahyuni Damanik; Antonius Remigius Abi; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article refers to the analysis of learning guidance on learning difficulties of fourth-grade students at SDN 091377 Purbatua Rambah in terms of qualitative methods and a case study approach to produce descriptive data in the form of written or spoken words from the subject and behaviour that could be observed to find out in detail. This is aimed to find out in-depth and find out the implementation of learning guidance on students’ learning difficulties. The informants in the study involved 5 informants in which one class representative teacher or supervisor was the key informant, two students who had learning difficulties were studied, one principal, and one class teacher. To find out the learning guidance implementation on students’ learning difficulties, the researchers observed the participant, in-depth interviews, and documentation. After the researchers conducted interviews, the researchers obtained that the implementation of guidance on students’ learning difficulties was carried out by the class representative teacher or supervisor teacher. The researchers analyzed students’ learning difficulties when students were inside and outside the classroom. When in the classroom, the teacher guided the students who have learning difficulties by telling students to sit in the front seat in order to be close to the teacher, then the teacher could pay more attention. When outside the classroom or during break time the teacher invited the students who have learning difficulties to come with the teacher to the office. And the students’ break time was used by the teacher to guide students to learn the material that students have not understood yet when studying in class. Learning guidance was only carried out during school hours and learning guidance was not a school program.